SUGAR AND Β-CAROTENE ACCUMULATION IN CARROT (DAUCUSCAROTA L.) TAP ROOTS AS INFLUENCED BY FERTILIZATION AND BIO-STIMULANT APPLICATION UNDER GREENHOUSE CONDITIONS. (2016) - M.M.S, Sekoli; J.C, Pretorius; G.M., Coetzer
No abstract available